ARCHITECTURAL CHANGES IN LIEPAJA’S CENTER DUE TO ECONOMIC CONDITIONS AND POLITICAL IDEOLOGY - Ozola, Silvija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
In Liepaja, until 1703 economic developed on the Trade Port channel’s southern embankment. The main traffic flow changed his direction: from the port to the New Market leads Great (Latvian: Lielā) Street, at which end a wooden bridge was built over the channel. In the 19th century, the Administrative Center formed at the New Market Square’s vicinity. Streets connected squares and green structures in a united system. The Rose Square was set up instead the New Market. During World War II, the building at embankments and Great Street was destroyed. Using the Master Plan, approved in 1950, architect Vladimir Kruglov created the Detailed Plan for developed of Liepaja Center and Great Street. A reinforced-concrete bridge was built across the channel. Until the 100th Anniversary of the Proclamation of Independence of Latvia, the bridge was expanded, but Great Street was reconstructed. The object of the research – the city center of Liepaja and Great Street. Research problem – architectural changes of the city center of Liepaja and Great Street has studied not sufficiently. Research novelty – architectural analysis of the city center of Liepaja and Great Street. The goal of the research – to determine the typical changes in planning of the city center and Great Street in the context of Liepaja urban development. Main methods applied – analysis of archive documents, projects and cartographic materials of urban planning, as well as study of published literature and inspection of buildings in nature.